The transformation to the parent function f(x) from g(x) is (b) g(x) is shifted 2 units to the right and 6 units up
The equations are given as:
f(x) = x^3
g(x) = (x - 2)^3 + 6
The function g(x) can be rewritten as:
g(x) = (x - h)^3 + k
This means that the function f(x) is shifted right by h units and shifted up by k units.
By comparison:
h = 2 and k = 6
Hence, the transformation to the parent function f(x) from g(x) is (b) g(x) is shifted 2 units to the right and 6 units up
Read more about function transformations at:
https://brainly.com/question/17586310
#SPJ1